Strategie rozwoju i wyzwania pielęgniarstwa w Polsce i na świecie - Bartosiewicz, Anna; Jacek, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Stale zmieniające się otoczenie oraz ciągle rosnące potrzeby i wymagania pacjentów sprawiają, że pielęgniarstwo definiuje swoje kompetencje, szuka swojego miejsca w systemie ochrony zdrowia z niezmienną misją, jaką jest ratowanie ludzkiego życia oraz opieka nad pacjentem. Dokonujące się stale zmiany w ochronie zdrowia, w społeczeństwie, a także w strukturach zawodów medycznych powodują, że pielęgniarstwo nieustannie dąży do swego rozwoju i stara się podejmować dialog merytoryczny z osobami odpowiedzialnymi za politykę zdrowotną celem nakreślenia ram funkcjonowania zawodu w aktualnej rzeczywistości oraz jego przyszłości. Przegląd strategii rozwoju pielęgniarstwa wielu krajów pozwala wnioskować o ich pozytywnym oddziaływaniu na zdrowie publiczne w danym kraju oraz na wzrost jakości opieki nad pacjentem. Ogromnym osiągnięciem dla pielęgniarstwa w Polsce jest inicjatywa stworzenia Strategii rozwoju dla pielęgniarstwa. Jest to pierwszy dokument o charakterze planistycznym, który określa kierunki działań zapewniające wysoką jakość, bezpieczeństwo i dostęp pacjentów do profesjonalnej opieki pielęgniarskiej.

Constantly changing environment and constantly growing needs and requirements of patients, make nursing define its competences, look for place in the health care system, plan tasks and create nursing development strategies. It tries to meet the requirements, becoming at the same time a key link in the health care system and a fully autonomous profession but with an unchangeable mission which is to save human life and care for the patient. Permanent changes in health care, in society as well as in the structures in medical professions cause that nursing constantly strives for its development and tries to engage substantive dialogue with those responsible for health policy, in order to outline the framework of the profession in the actual reality and its future. A review of selected national strategies for nursing development, the circumstances in which they developed and key assumptions allow to conclude about their positive impact on public health in a given country and on the quality of patient care. What connects individual strategies is the priority treatment of multisectoral cooperation in health care, aspects related to the promotion of the profession, education of nurses and the definition of new roles and new competences in the context of the requirements and needs of a given country. An example may be prescribing, providing nursing advice or introducing the role of an advanced practice nurse. A great achievement for nursing in Poland is the initiative of creation Strategy of Development for nursing. It is a planning document that defines the directions of activities ensuring high quality, safety and access to nursing care of patients.
Keywords: niedobór kadry pielęgniarskiej; strategia rozwoju; pacjent; nursing shortage; development strategy; patient